Why do people watch others play video games? An empirical study on the motivations of Twitch users. (October 2017) - Sjöblom, Max; Hamari, Juho
Abstract: This study investigates why people choose to watch others play video games, on services such as Twitch. Through a questionnaire study (N = 1097), we examine five distinct types of motivations from the uses and gratifications perspective: cognitive, affective, personal integrative, social integrative and tension release. Information seeking is shown to be positively associated with the amount of hours that users chose to spend on the service, as well as the amount of individual streamers they choose to watch. Furthermore, we find that tension release, social integrative and affective motivations are positively associated with how many hours people watch streams. We also find that social integrative motivations are the primary predictor of subscription behaviour. This study lays the groundwork for understanding the motivations to consume this emerging form of new media in the context of online games and video streams. Highlights: The study lays groundwork for understanding video stream consumer motivations. Tension release strong positive impactor on hours watched for video game streams. Social integrative motivations found to impact subscription behaviour. Informating seeking shown to impact number of streamers watched.